Stabilization of chaotic dynamics emerging in an economy with international labor migration - Giovanni Bella; Paolo Mattana; Beatrice Venturi (Social Sciences and Humanities Open)
This paper examines the conditions for the emergence of chaotic dynamics in the economy described by Parello (2019) and the role of international labor migration on the global indeterminacy of the equilibrium resulting from the competition in the labor market between native workers and immigrants entering a host country. The application of the Shilnikov theorem reveals the spiraling structure of the chaotic attractor, allowing us to infer the unpredictability of long-run policies amid international labor migration. We also propose an approach to control this chaotic scenario and stabilize the economic dynamics towards a stable equilibrium by applying the algorithm proposed by Ott et al. (1990), to determine the necessary conditions and exact parametric configuration to redirect the economy along the optimal path that avoids the undesired indeterminate solution.